Răspuns :
Daca x-3 si y+2 sunt numere naturale , atunci :
x-3={ 1 ; 2 ; 3 ; 4 ; 6 ; 12} ⇒ x = { 4 ; 5 ; 6 ; 7 ; 9 ; 15} fata de care ...
y+2={12 ; 6 ; 4 ; 3 ; 2 ; 1 } ⇒ y = {10 ; 4 ;2 ; 1 ; -1}
x-3={ 1 ; 2 ; 3 ; 4 ; 6 ; 12} ⇒ x = { 4 ; 5 ; 6 ; 7 ; 9 ; 15} fata de care ...
y+2={12 ; 6 ; 4 ; 3 ; 2 ; 1 } ⇒ y = {10 ; 4 ;2 ; 1 ; -1}
Daca x-3 si y+2 sunt numere naturale , atunci :
x-3={ 1 ; 2 ; 3 ; 4 ; 6 ; 12} ⇒ x = { 4 ; 5 ; 6 ; 7 ; 9 ; 15} fata de care ...
y+2={12 ; 6 ; 4 ; 3 ; 2 ; 1 } ⇒ y = {10 ; 4 ;2 ; 1 ; -1}
x-3={ 1 ; 2 ; 3 ; 4 ; 6 ; 12} ⇒ x = { 4 ; 5 ; 6 ; 7 ; 9 ; 15} fata de care ...
y+2={12 ; 6 ; 4 ; 3 ; 2 ; 1 } ⇒ y = {10 ; 4 ;2 ; 1 ; -1}